CompTIA IT fundamentals+ exam guide, (exam FC0-U61) - Meyers, Mike 1961-; Jernigan, Scott; Lachance, Daniel (McGraw-Hill Education, 2019)
This fully updated study guide delivers 100% coverage of every topic on the 2018 CompTIA IT Fundamentals+ exam. Take the CompTIA IT Fundamentals+ exam with complete confidence using this effective self-study system. Written by three CompTIA certification and training experts, this authoritative guide explains foundational computer technologies in full detail. You'll find learning objectives at the beginning of each chapter, exam tips, practice exam questions, and in-depth explanations throughout. Designed to help you pass the exam with ease, this definitive volume also serves as an essential on-the-job reference.
Includes index. - Online resource; title from title page (Safari, viewed May 31, 2019)
Keywords: Computer science -- Study guides -- Examinations; Information technology -- Study guides -- Examinations; Computer technicians -- Study guides -- Certification; Informatique; Examens; Guides de l'étudiant; Computer science; Examinations; Computer technicians; Certification; Information technology; Examinations; examination study guides; Study guides; Guides de l'étudiant